Foam sensor with ultra-wide tensile strain sensing range and preparation and application thereof
By using mechanical mixing of micron-scale matrix particles and conductive fillers and supercritical carbon dioxide foaming technology in porous flexible sensors, foam sensors with ultra-wide tensile strain detection range and high sensitivity are prepared, solving the sensor performance in the prior art The problem of insufficient has achieved effective use in various applications.
Patent Information
- Application Number
- CN202411358284.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Existing porous flexible sensors have shortcomings in the tensile strain detection range and sensitivity, making it difficult to achieve ultra-wide working range and high sensitivity. In particular, the selection and distribution of conductive fillers have a great impact on sensor performance, and the sensor preparation process is complex, so organic is used. Solvent.
Micron-scale matrix particles and conductive filler are mechanically mixed in a drum with steel balls to form composite particles. A foam sensor with isolation structure and gradient pore structure is prepared through thermal compression molding and supercritical carbon dioxide foaming technology. The conductive filler is evenly distributed in The interface between the substrate particles forms a three-dimensional conductive network.
Achieved with an ultra-wide tensile strain detection range (up to 762%) and high sensitivity, the sensor exhibits excellent tensileability and durability in a variety of applications, suitable for human motion monitoring and smart devices.
Smart Images

Figure CN119264506A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of tensile strain foam sensors, and in particular to a foam sensor with an ultra-wide tensile strain sensing range, a preparation method and an application thereof. Background Art
[0002] Flexible sensors have broad application prospects in the fields of wearable electronics and human-computer interaction and are developing rapidly. Strain sensors have attracted widespread attention due to their low cost and simple structure. Sensors based on metal and semiconductor materials usually have a low strain response range due to their poor stretchability, which limits their application in many scenarios. Thanks to the excellent stretchability and stretch recovery rate of elastomers, they are often used as the matrix of strain sensors (such as polyolefin elastomers (POE), polydimethylsiloxane (PDMS) and thermoplastic polyurethane (TPU)). Tensile strain sensors with a wide response range and high sensitivity are still a major development direction.
[0003] Porous structure sensors have been widely developed in recent years due to their light weight and good air permeability. They are mainly prepared by freeze drying, template method, impregnation, etching and chemical vapor deposition (CVD) and gradually face complex processes and the use of organic solvents. However, it is a great challenge to realize porous flexible electronic devices with a wide strain range. Jeong et al. made a porous structured flexible sensor by CVD method, but the stretching rate was low, only 77% strain. Wang et al. prepared TPU / MWCNTs@MXene foam sensor by salt template method, with a sensitivity of 363, but the strain detection range was only 100%. The detection ranges of porous sensors reported by Gong et al. and Yuan et al. were 250% and 221% strain, respectively, but there is still room for further improvement. Although Zhang et al. developed a negative Poisson's ratio porous metamaterial with an ultra-wide response range (1200% strain) by freeze drying, its sensitivity was low, and the relative resistance change at 1200% strain was only ~60. Therefore, there is an urgent demand for flexible porous sensors with ultra-wide detection range and high sensitivity.
[0004] Sensors with a wide operating range usually require good stretchability and high conductivity. However, in randomly distributed structured conductive elastomer composites (CECs), high conductivity composites need to be loaded with a large amount of conductive fillers, but their tensile properties are severely deteriorated. Although CECs with less conductive fillers have large tensile strain, their conductivity is low. Therefore, a trade-off needs to be made between good stretchability and high conductivity. In addition, the type of conductive filler plays a crucial role in the operating range of the sensor. Generally, conductive fillers with low aspect ratios exhibit high percolation thresholds and low conductivity. In addition, due to the high aspect ratio, 1D fillers usually have lower sensitivity than 2D and 0D fillers. Therefore, high aspect ratio conductive fillers are beneficial to improve the operating range of the sensor. Carbon nanostructures (CNS) are a new type of branched multi-walled carbon nanotubes with a high aspect ratio. Supercritical CO2 (scCO2) foaming, using scCO2 as a foaming agent, is a simple, green and environmentally friendly method for preparing porous materials. There are many studies on the preparation of compression sensors using scCO2 foaming, but there are few studies on tensile strain sensors.
[0005] In summary, it is of great significance to develop a porous tensile strain sensor with ultra-wide working range and high sensitivity. Summary of the invention
[0006] In view of the above technical problems and the deficiencies in the art, the present invention provides a foam sensor with an ultra-wide tensile strain sensing range, and a preparation method and application thereof.
[0007] The technical solution of the present invention is introduced below:
[0008] [1] A method for preparing a foam sensor with an ultra-wide tensile strain sensing range, comprising the steps of:
[0009] (1) adding micrometer-sized matrix particles and conductive fillers into a drum with steel balls, and mechanically mixing them so that the conductive fillers are evenly coated on the surface of the matrix particles to obtain composite particles;
[0010] (2) hot compression molding the composite particles in a flat vulcanizer to obtain a composite material with an isolation structure;
[0011] (3) keeping the composite material in a physical foaming agent at a constant temperature and pressure, releasing the pressure to foam, and cooling to set the composite material, thereby obtaining the foam sensor having an ultra-wide tensile strain sensing range;
[0012] The thickness of the foam sensor is 0.1 to 1 mm, further 100 to 700 micrometers, for example, any value among 0.1 mm, 0.3 mm, 0.5 mm, 1 mm, or a range between any two of the above;
[0013] The foam sensor has a porous structure, and in the thickness direction of the foam sensor, the foam sensor presents a gradient structure in which the size of the foam cells gradually increases from the two end surfaces to the center.
[0014] The preparation method of the present invention requires the use of micron-sized matrix particles to produce the foam sensor of the above thickness. Only at the above thickness can the foam sensor of the present invention show a gradient structure in which the pore size gradually increases from the two end surfaces to the center in the thickness direction and has an ultra-wide tensile strain sensing range.
[0015] The matrix particles of the present invention are small in size and difficult to mix with the conductive filler. Simple dry mixing is difficult to achieve the selective and uniform distribution of the conductive filler at the interface between the micron-sized matrix particles. In order to fully mix the micron-sized matrix particles with the conductive filler, the preparation method of the present invention uses a roller with steel balls to achieve full mixing of the matrix particles and the conductive filler. According to the preparation method of the present invention, in the foam sensor, the conductive filler is selectively and uniformly distributed at the interface between the micron-sized matrix particles to form a three-dimensional conductive network.
[0016] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (1), the matrix particles may include at least one of thermoplastic polyurethane elastomer particles, thermoplastic polyamide elastomer particles, thermoplastic polyester elastomer particles, polyolefin elastomer (POE) particles, and natural rubber particles, preferably including polyolefin elastomer (POE) particles.
[0017] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (1), the average particle size of the matrix particles is preferably 20 to 1000 microns, more preferably 100 to 1000 microns, such as 380 microns. If the average particle size of the particles is too small, the specific surface area will increase and more conductive fillers need to be added; if the particle size is too large, the interfacial strength of the bonding between the particles will be reduced, which will seriously damage the stretchability of the material.
[0018] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (1), the conductive filler may include at least one of carbon black (CB), silver nanowires, carbon nanotubes, branched carbon nanotubes (CNS), graphene (G), reduced graphene oxide (rGO), and MXene, preferably including branched carbon nanotubes (CNS).
[0019] [1] The method for preparing a foam sensor with an ultra-wide tensile strain sensing range described in step (1), based on the total mass of the matrix particles and the conductive filler as 100%, the mass percentage of the conductive filler is preferably 0.1% to 10%, and more preferably 0.5% to 10%, for example, any value among 0.1%, 0.3%, 0.5%, 1.5%, 3%, 6%, 10%, or a range between any two of the above. When too little filler is added, the insulation or conductivity of the composite material is very poor, and the material does not have piezoresistive sensing capability or has a narrow sensing range; when too much filler is added, the thickness of the conductive layer on the particle surface increases, which hinders the mutual diffusion of POE molecular chains between particles during the molding process, reduces the interface strength, thereby damaging the stretchability of the material, and further reducing the detection range of the strain sensor.
[0020] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (1), the mechanical mixing time can be 1 to 360 minutes.
[0021] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (2), the temperature of the hot compression molding can be 50 to 90°C, and the pressure can be 9 to 11 MPa, for example, 10 MPa.
[0022] In the method for preparing the foam sensor with an ultra-wide tensile strain sensing range described in [1], step (3) may adopt an intermittent foaming method.
[0023] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (3), the physical foaming agent may include at least one of carbon dioxide and nitrogen.
[0024] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, the mass percentage of the physical foaming agent in the composite material is preferably 0.5% to 10%.
[0025] In some embodiments, in the method for preparing a foam sensor with an ultra-wide tensile strain sensing range described in [1], in step (3), the physical foaming agent includes carbon dioxide and nitrogen. Furthermore, in the physical foaming agent, the volume ratio of the carbon dioxide to the nitrogen may be 99:1 to 1:99.
[0026] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (3), the heat preservation and pressure holding temperature is preferably 30 to 80°C, such as 50°C, the pressure holding pressure is preferably 7 to 20 MPa, and the heat preservation and pressure holding time is preferably 30 to 120 minutes, such as 60 minutes. The sample can be saturated with carbon dioxide in a short time.
[0027] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (3), the time for decompression and foaming is preferably no more than 10 seconds, such as 2-3 seconds. Rapid decompression can increase the driving force for cell nucleation, improve cell density and reduce cell size.
[0028] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (3), the foaming ratio of the composite material in the foaming process of step (3) is preferably 1.1 to 4 times, such as 2 times. The foam sensor has porosity and exhibits excellent stretchability.
[0029] [1] In the method for preparing a foam sensor with an ultra-wide tensile strain sensing range, in step (3), the average cell size of the foam sensor is preferably 10 to 300 microns, such as 15 microns. Microporous foam materials have more excellent mechanical properties.
[0030] [2] A foam sensor having an ultra-wide tensile strain sensing range prepared according to the preparation method described in [1].
[0031] The foam sensor of the present invention has an ultra-high strain detection range and can reach 762% tensile strain.
[0032] [3] Application of the foam sensor according to [2] in a tensile strain sensing device.
[0033] [4] The foam sensor described in [2] is used as a tensile strain sensor in human motion monitoring, human-computer interaction, health monitoring, and intelligent robots.
[0034] The foam sensor of the present invention can be applied to a full range of motion detection, including facial expressions, running, fitness and other sports for good monitoring.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention develops a simple, environmentally friendly, and mass-producible strategy to prepare foam sensors with an ultra-wide tensile strain response range by combining micron-sized flexible polyolefin elastomer (POE) and other matrix particles with conductive branched carbon nanotubes (CNS) and other conductive fillers. A flexible and waterproof foam sensor using POE / CNS as an example with an isolation structure and a gradient pore structure is prepared using physical foaming techniques such as supercritical carbon dioxide (scCO2).
[0037] The foam sensor of the present invention has the characteristics of ultra-wide tensile strain response range (e.g., 0.5% to 763%), high sensitivity (exemplarily, the specification factor GF is 15230), fast response time (exemplarily, 200 milliseconds), good resilience, durability, etc. Therefore, the foam sensor of the present invention with a porous structure exhibits monitoring of all-round human body movements, even underwater, and plays a role in playing badminton and fitness.
[0038] The present invention develops a simple, mass-producible, green method to prepare a foam sensor with a wide working range and high sensitivity, which strongly promotes the development of sensors in practical applications. According to one aspect of the present invention, a foam strain sensor is provided, the foam strain sensor comprising a conductive filler and a matrix, the conductive filler being coated on the surface of a thermoplastic elastomer particle matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a cross-sectional morphology photograph of the isolated structure POE / CNS composite material with a CNS content of 3 wt% in Example 1.
[0040] Figure 2 This is a cross-sectional morphology photograph of the center area in the thickness direction of the foam with a CNS content of 3 wt% in Example 1.
[0041] Figure 3 This is a photograph of the gradient pore structure near the bottom in the thickness direction of the foam with a CNS content of 3 wt% in Example 1.
[0042] Figure 4 This is the stress-strain curve of the insulating structural foam with a CNS content of 3 wt % in Example 1.
[0043] Figure 5 This is a tensile strain sensing curve of the isolation structural foam with a CNS content of 3 wt % in Example 1.
[0044] Figure 6 This is a piezoresistance curve of the isolation structure foam with a CNS content of 3 wt% in Example 1 under 800% stretching cycle.
[0045] Figure 7 This is the response time diagram of the isolation structure foam with a CNS content of 3 wt% in Example 1.
[0046] Figure 8 This is a cross-sectional morphology photograph of the randomly distributed structural foam with a CNS content of 3 wt% in Example 2.
[0047] Fig. 9 This is the piezoresistance curve of the randomly distributed structural foam with a CNS content of 3 wt% in Example 2. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0049] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.
[0050] Example 1
[0051] First, the branched carbon nanotube CNS particles are placed in a mechanical mixer and mixed for 10 minutes so that the particles are crushed by steel balls. Then, polyolefin elastomer POE particles with an average particle size of 380 microns are added to the mechanical mixer and mixed for another 30 minutes to obtain CNS@POE particles with an average particle size of about 400 microns. A certain amount of CNS@POE particles are placed in a mold and hot-pressed at 90°C in a flat vulcanizer with a molding pressure of 10 MPa to obtain a POE / CNS composite material with an isolation structure having a thickness of about 300 microns, wherein the mass fraction of CNS is 3wt%, based on the total mass of the matrix particles and the conductive filler as 100%. The conductive filler CNS is selectively and evenly distributed at the interface between the micron-sized POE matrix particles to form a three-dimensional conductive network, such as Figure 1 The sample can be recorded as POE / CNS composite or CNS3.
[0052] The composite material prepared above was placed in an autoclave, carbon dioxide was injected to expel the air in the autoclave, and then carbon dioxide was filled again to make the pressure in the autoclave reach 20MPa. Saturated at 50°C for one hour, followed by rapid pressure relief, the process took about 2-3 seconds, and the obtained foam sample was placed in ice water to cool to stabilize the pore structure, and finally a foam sensor with an isolation structure and a gradient pore structure was obtained, which can be recorded as POE / CNS composite foam material or FCNS3, with a thickness of 500 microns. The foaming ratio of the foam is about 2 times, and the average pore size is about 15 microns. Figure 2 and Figure 3 As shown, the foam has a uniformly distributed pore structure, and along the thickness direction, from the skin layer to the core layer, the pore size gradually increases, presenting a gradient pore structure.
[0053] The tensile properties of POE / CNS composite foam materials were tested on a universal material testing machine. The material size was 35 mm long, 2 mm wide, 0.5 mm thick, and the tensile rate was 10 mm / min. The cyclic tensile test of POE / CNS composite foam materials was conducted on a universal material testing machine. The sample size of the foam sample was 6 cm long, 1 cm wide, and about 0.5 mm thick. The cyclic tensile rate was 50 mm / min. Figure 4As shown in Figure 2, the isolated structure POE / CNS foam exhibits excellent stretchability, with an elongation at break of up to 952%. Figure 5 As shown in the figure, during the stretching process, as the tensile strain increases, the relative resistance of the foam sensor gradually increases, showing an ultra-high sensitivity in the strain range of 700%-762%, with a GF as high as 15230, and also showing an ultra-wide strain detection range from 0.5% to 762% strain. Figure 6 As shown, during the stretching cycle, the relative resistance of the foam sensor first increases with the increase of the tensile strain, and then gradually decreases during the return process. Due to the existence of residual strain, the resistance cannot return to the initial value. Figure 7 It was shown that the foam sensor has a very short response time, as low as 200ms.
[0054] The strain sensing performance of POE / CNS foam was tested by an electrochemical workstation with an output voltage of 1V and a point taken every 0.1s. The size of the foam sample used for the test was 6cm long, 1cm wide and 0.5mm thick. When the foam sensor was cyclically stretched on a universal material testing machine, a computer connected to the electrochemical workstation recorded the current changes of the sample.
[0055] Example 2
[0056] POE and CNS were placed in an internal mixer and blended at 90°C for 8 minutes, with the rotor rotating at a speed of 50 rpm. A POE / CNS composite material was obtained, wherein the total mass of POE and CNS was 100%, and the mass fraction of CNS was 3wt%. The obtained POE / CNS composite material was formed by a flat vulcanizer at 15MPa and 90°C to finally obtain a sheet-like POE / CNS composite material.
[0057] The composite material prepared above was placed in an autoclave, carbon dioxide was injected to expel the air in the autoclave, and then carbon dioxide was refilled to make the pressure in the autoclave reach 20MPa. Saturation was carried out at 50°C for one hour, followed by rapid pressure release for about 2-3 seconds. The obtained foam sample was placed in ice water to cool to stabilize the pore structure, and finally a randomly distributed POE / CNS foam sensor r-FCNS3 was obtained. The obtained sensor thickness was about 500 microns. Figure 8 As shown, the randomly distributed POE / CNS foam has a uniform pore structure, and the conductive filler is evenly dispersed in the pore wall.
[0058] The cyclic tensile test of the randomly distributed POE / CNS composite foam material was carried out on a universal material testing machine. The sample size of the foam sample was 6 cm long, 1 cm wide, and about 0.5 mm thick. The cyclic tensile rate was 50 mm / min. Fig. 9As shown, with the increase of tensile strain, the relative resistance of the sensor first decreases and then increases, and there is a narrow strain sensing range of only about 150% strain, which is much lower than the strain sensing range of the isolated structure POE / CNS foam sensor.
[0059] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing a foam sensor with an ultra-wide tensile strain sensing range, characterized in that: Includes steps: (1) adding micrometer-sized matrix particles and conductive fillers into a drum with steel balls, and mechanically mixing them so that the conductive fillers are evenly coated on the surface of the matrix particles to obtain composite particles; (2) hot compression molding the composite particles in a flat vulcanizer to obtain a composite material with an isolation structure; (3) keeping the composite material in a physical foaming agent at a constant temperature and pressure, releasing the pressure to foam, and cooling to set the composite material, thereby obtaining the foam sensor having an ultra-wide tensile strain sensing range; The thickness of the foam sensor is 0.1 to 1 mm, further 100 to 700 microns; The foam sensor has a porous structure, and in the thickness direction of the foam sensor, the foam sensor presents a gradient structure in which the size of the foam cells gradually increases from the two end surfaces to the center.
2. The preparation method according to claim 1, characterized in that: In step (1): The matrix particles include at least one of thermoplastic polyurethane elastomer particles, thermoplastic polyamide elastomer particles, thermoplastic polyester elastomer particles, polyolefin elastomer particles, and natural rubber particles; The average particle size of the matrix particles is 20 to 1000 microns, further 100 to 1000 microns; The conductive filler comprises at least one of carbon black, silver nanowires, carbon nanotubes, branched carbon nanotubes, graphene, reduced graphene oxide, and MXene; Taking the total mass of the matrix particles and the conductive filler as 100%, the mass percentage of the conductive filler is 0.5% to 10%.
3. The preparation method according to claim 1, characterized in that: In step (1), the mechanical mixing time is 1 to 360 minutes.
4. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the hot compression molding is 50 to 90° C. and the pressure is 9 to 11 MPa.
5. The preparation method according to claim 1, characterized in that: Step (3) adopts intermittent foaming method; In step (3): The physical foaming agent includes at least one of carbon dioxide and nitrogen; The mass percentage of the physical foaming agent in the composite material is 0.5% to 10%.
6. The preparation method according to claim 1 or 5, characterized in that: In step (3), the physical foaming agent includes carbon dioxide and nitrogen; In the physical foaming agent, the volume ratio of the carbon dioxide to the nitrogen is 99:1 to 1:
99.
7. The preparation method according to claim 1 or 5, characterized in that: In step (3): The heat preservation and pressure preservation are performed at a temperature of 30 to 80° C. and a pressure of 7 to 20 MPa. The heat preservation and pressure holding time is 30 to 120 minutes; The pressure relief and foaming time does not exceed 10 seconds; In step (3), the foaming ratio of the composite material during the foaming process is 1.1 to 4 times; The average cell size of the foam sensor is 10 to 300 microns.
8. A foam sensor with an ultra-wide tensile strain sensing range prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the foam sensor according to claim 8 in a tensile strain sensing device.
10. Application of the foam sensor according to claim 8 as a tensile strain sensor in human motion monitoring, human-computer interaction, health monitoring, and intelligent robots.
Citation Information
Patent Citations
Flexible strain material capable of being stretched and compressed simultaneously as well as preparation method and application of flexible strain material
CN116162284A
Elastomer foam sensor and preparation method and application thereof
CN117384478A
Piezoresistive foam based on macroscopic isolation structure and preparation and application thereof
CN117946446A
Polymer foam and method for preparing the same
US20170029589A1
Cited By
Preparation method of polymer bead foam sensor with isolation structure
CN121319455A